Safety and efficacy of cold polypectomy compared to endoscopic mucosal resection and hot biopsy polypectomy. (4th May 2019) - Iwashita, Hideyuki; Takedatsu, Hidetoshi; Murao, Hiroyuki; Funakoshi, Sadahiro; Kuniki, Yasuhisa; Matsuoka, Satoshi; Tsukamoto, Shinji; Yamaguchi, Masashi; Shakado, Satoshi; Kabemura, Teppei; Sakisaka, Shotaro
Abstract: Backgrounds: Recently, several studies have demonstrated the usefulness of cold polypectomy (CP), a safe and simple method for the removal of small polyps. We investigated the safety and efficacy of CP compared to that of endoscopic mucosal resection (EMR) and hot biopsy polypectomy (HB). Methods: We retrospectively examined 1713 colorectal polyps (size 1–9 mm) in 731 patients. CP, EMR, and HB were performed on 476, 997, and 240 lesions, respectively. We compared the region, size, morphology, the presence of delayed bleeding as overt bleeding 24 h after operation, number of clips, pathology, the presence of antithrombotic therapy, procedure time from detection of a polyp to resection and hemostasis, device cost including device and clips, and polyp remnants. Results: The delayed bleeding in the CP group (0/476) was significantly lower compared to that in the HB group (3/240) and EMR group (7/997). There were no cases of perforations. The procedure time was significantly shorter in the CP group than in the EMR group (91.3sec vs 290.1sec, p < .0001). The CP group had a significantly lower device cost than the HB and EMR groups (49.2USD vs 58.0 USD vs 91.3 USD, p < .0001) was not inferior in terms of polyp remnants to the EMR and HB groups. (1.4% vs 0.6% vs 6.1%, p = .1599) Conclusions: CP is a safe treatment that achieves less delayed bleeding. Moreover, CP is not inferior to other groups in terms of polyp remnants and offers a cost benefit. CP can be considered useful for colonic polypectomy.